ANALISIS PENGARUH KECUKUPAN MODAL, LIKUIDITAS DAN RISIKO KREDIT TERHADAP KINERJA KEUANGAN DAN PENYALURAN KREDIT PADA PT. BANK MALUKU MALUT - Indayanti sanggel (Soso-Q : Jurnal Manajemen, 2019)
This study aims to analyze the effect of capital adequacy, liquidity and credit risk on financial performance measured using ROA and lending.The population in this study is the Maluku Maluku bank in the period 2008-2015. The number of samples used is 10-year quarterly data. The method used in this research is multiple linear regression analysis with hypothesis testing, namely normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, T test, F test using SPSS program.This shows that the CAR variable has no effect on ROA, the LDR variable has no effect on ROA, the NPL variable has no effect on ROA, the CAR variable has no effect on total credit, the LDR variable has an effect on total credit, the NPL variable has no effect on total credit. Keywords: CAR, LDR, NPL, ROA, TOTAL CREDIT